1993
DOI: 10.1002/bjs.1800800528
|View full text |Cite
|
Sign up to set email alerts
|

Management of non-functioning neuroendocrine tumours of the pancreas

Abstract: Between 1982 and 1991, 20 patients of median age 44 (range 22-76) years were treated for non-functioning neuroendocrine tumours of the pancreas. Presenting features were obstructive jaundice (seven patients), abdominal pain (seven), weight loss (six), abdominal mass (eight) and severe haemorrhage (four). Gut hormone profiles were normal except for one patient who had a raised pancreatic polypeptide level. Contrast-enhanced computed tomography localized the tumour in 17 patients and visceral angiography in 14 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 9 publications
0
30
0
Order By: Relevance
“…Abdominal pain is the major presenting symptom (35–78%), followed by weight loss (20–35%), anorexia and nausea (45%). The patient may present with intra-abdominal hemorrhage (4–20%), jaundice (17–50%) or a palpable mass (7–40%) [21,22,23,24,25]. Fifty-nine percent to 80% of the patients present with synchronous liver metastases at diagnosis [10, 25].…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal pain is the major presenting symptom (35–78%), followed by weight loss (20–35%), anorexia and nausea (45%). The patient may present with intra-abdominal hemorrhage (4–20%), jaundice (17–50%) or a palpable mass (7–40%) [21,22,23,24,25]. Fifty-nine percent to 80% of the patients present with synchronous liver metastases at diagnosis [10, 25].…”
Section: Introductionmentioning
confidence: 99%
“…The most common symptoms include: abdominal pain (35-78%), weight loss (20-35%), loss of appetite and vomiting (45%). Less common are internal haemorrhages (4-20%), jaundice (17-50%) or palpable tumours in the abdomen (7-40%) [2,[24][25][26]. Recent studies by Italian researchers have demonstrated that hepatic metastases are observed in 32% of patients with a newly diagnosed NF-PNEN [27].…”
Section: Clinical Characteristics Of Pnenmentioning
confidence: 99%
“…The common cystic appearance on CT is explained by central necrosis of these slow-growing tumours. They can be vascular lesions which blush on angiography and mimic nonfunctioning neuroendocrine tumours of the pancreas [12]. They tend to ulcerate into the small bowel causing either iron-deficiency anaemia or frank gastrointestinal haemorrhage.…”
Section: Discussionmentioning
confidence: 99%